THE TREATMENT OF DYSMENORRHEA AMONG ADOLESCENT FEMALES - Suwarsih, Meli; Ari Astuti, Dhesi; Fitriahadi, Enny (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
AbstractDysmenorrhea occurs in women during the menstrual cycle is not highly dangerous or life-threatening. However, it does affect daily activities, especially among students and their learning activities. This negative effect is due to the rising pain, which is highly disruptive and could negatively impact the quality of life, including health, concentration, and learning motivation. This research utilized a qualitative approach in which an in-depth interview was conducted to uncover the informants' strategies for managing dysmenorrhea by applying a phenomenological approach to analyze the data. The informants were selected through purposive sampling. Further, this study included six adolescent females with dysmenorrhea, six informants' parents, one school health unit manager, and one librarian. The data collection tool, an interview guide, was subjected to a pilot interview and the data analysis was facilitated by the NVivo software program. This research generates two themes: (1) Health oriented treatment strategies and (2) Perspective-based treatment strategies. Adolescent females pursue Health-oriented management strategies mainly pharmacologically, which involves using medications such as Ibuprofen, Paracetamol, and Feminax. Besides, these adolescent females alleviate dysmenorrhea through cultural perspectives using herbal remedies such as warm ginger milk, turmeric tamarind, clove oil, and warm compresses, and only a few of them would seek a medical examination from healthcare facilities.Keywords: Treatment, Dysmenorrhea, Adolescent Females